Inducing differentiation of transformed cells with hybrid polar compounds: a cell cycle-dependent process. - Marks, P A (1994)
Transformed cells do not necessarily lose their capacity to differentiate. Various agents can induce many types of neoplastic cells to terminal differentiation. Among such inducers, a particularly potent group consists of hybrid polar compounds; hexamethylene bisacetamide (HMBA) is the prototype of this group. With virus-transformed murine erythroleukemia cells as a model, HMBA was shown to cause these cells to arrest in G1 phase and express globin genes. This review focuses on HMBA-induced modulation of factors regulating G1-to-S phase progression, including a decrease in the G1 cyclin-dependent kinase cdk4, associated with inhibition of phosphorylation of the retinoblastoma protein pRB and possibly other related proteins that, in turn, sequester factors required for initiation of DNA synthesis; this provides a possible mechanism for HMBA-induced terminal cell division. Evidence that hybrid polar compounds have therapeutic potential for cancer treatment will also be reviewed.